Oculocutaneous Albinism Type 7 with Recurrent Infections: A Case Report - Kilic, Mehmet; Ozcan, Mehmet Hazar; Taskin, Erdal; Yildirim, Hakan; Sen, Askin (Bilimsel Tip Yayinevi, 2021)
Oculocutaneous albinism (OCA) is a disorder of melanin biosynthesis characterized by hypopigmentation of the skin, hair, and retinal pigment epithelium. We present the clinical and laboratory features of two siblings, born to consanguineous Turkish parents, who were diagnosed with autosomal recessive OCA type 7. We detected a homozygous mutation in the C10ORF11 gene (p.A23Rfs * 39) in both patients. Interestingly, the medical history revealed that both patients had suffered from recurrent respiratory tract infections since birth. The patients were investigated for suspected immunodeficiency and the results of the immune screening assays were normal. We believe these patients are noteworthy to report since presentation with infections has not been described in the prior descriptions of OCA type 7. As of this current writing, infectious problems have stopped in one of our cases since the age of five and a half years.
Keywords: Oculocutaneous albinism type 7; recurrent infection; immune system; genetic analysis; C10ORF11 gene